#### Answer

u = 25
v = 1

#### Work Step by Step

Multiply the first equation by 3
3u - 90v = -15
Add to the second equation
3u - 90v = -15
-3u + 80v = 5
-10v = -10
v = 1
Plug v = 1 into 3u - 90v = -15
3u - 90 = -15
3u = 75
u = 25

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

u = 25
v = 1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.